FIRST RECORD OF FORENSIC SPECIES CONICERA SIMILIS (Haliday, 1833) (DIPTERA: PHORIDAE) ON EXHUMED RABBIT CARCASSES IN TURKEY - Karapazarlioglu, Ersin; Disney, R. Henry L. (European Scientific Journal, ESJ, 2015)
Scuttle fly is often observed in forensic cases especially on buried remains. Two genus of Phoridae is very important for buried remains in forensic cases. One of them is Conicera sp., and its literature is very limited. The aim of this study is to find the Conicera sp. in buried carcasses. Two rabbit carcasses were used as bait in Ankara province of Turkey. The insects collected included Conicera similis (Haliday, 1833) (Diptera, Phoridae), which was recorded for the first time in Turkey after the carcasses were exhumed in 45 days